2020
DOI: 10.1111/nph.16946
|View full text |Cite|
|
Sign up to set email alerts
|

Strong photoperiod sensitivity is controlled by cooperation and competition among Hd1, Ghd7 and DTH8 in rice heading

Abstract: Rice (Oryza sativa) is a short-day (SD) plant originally having strong photoperiod sensitivity (PS), with SDs promoting and long days (LDs) suppressing flowering. Although the evolution of PS in rice has been extensively studied, there are few studies that combine the genetic effects and underlying mechanism of different PS gene combinations with variations in PS. We created a set of isogenic lines among the core PS-flowering genes Hd1, Ghd7 and DTH8 using CRISPR mutagenesis, to systematically dissect their ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
100
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(120 citation statements)
references
References 51 publications
2
100
0
Order By: Relevance
“…In A. thaliana, HAP3b subunits can directly interact with Hd1/CO through its CCT-domain, forming CCAAT-binding CBF complexes that bind to FT promoters and activate transcription to promote flowering under LD [66,67]. In rice, the grass-specific gene Ghd7 is upregulated by a Ghd8-OsHAP5b-Hd1 complex under LD, enabling Ghd7 to suppress Ehd1 and delay flowering [36,63,[68][69][70][71][72]. However, Hd1/CO also competes with the complexes to promote Hd3a/RFT1 expression, creating a tradeoff relationship for photoperiod sensitive flowering under SD conditions.…”
Section: Discussionmentioning
confidence: 99%
“…In A. thaliana, HAP3b subunits can directly interact with Hd1/CO through its CCT-domain, forming CCAAT-binding CBF complexes that bind to FT promoters and activate transcription to promote flowering under LD [66,67]. In rice, the grass-specific gene Ghd7 is upregulated by a Ghd8-OsHAP5b-Hd1 complex under LD, enabling Ghd7 to suppress Ehd1 and delay flowering [36,63,[68][69][70][71][72]. However, Hd1/CO also competes with the complexes to promote Hd3a/RFT1 expression, creating a tradeoff relationship for photoperiod sensitive flowering under SD conditions.…”
Section: Discussionmentioning
confidence: 99%
“…This view is supported by the observation that a functional Ghd7 , DTH8 and Hd1 combination showed significantly stronger photoperiod sensitivity than other combinations in both near‐isogenic lines and natural populations (Zhang et al ., 2015; Wang et al ., 2019; Z.Y. Zhang et al ., 2019; Zong et al ., 2021), although there might be other types of transcriptional or post‐transcriptional regulation involving one or more of them (Wang et al ., 2019). For example, Hd1, DTH8 and distinct NF‐YC subunits reported to form a trimeric complex that bound to the CO Response Element 2 ( CORE2 ) in the Hd3a promoter, and Days to heading 7 (DTH7, also known as Hd2, OsPRR37 or Ghd7.1, another CCT domain‐containing protein strongly repressing flowering) can replace Hd1 in the complex (Goretti et al ., 2017).…”
Section: Transcriptional and Post‐transcriptional Regulation Of Key Hmentioning
confidence: 99%
“…Hd1 also loses LD heading suppression function and consistently promotes flowering under SD and LD in Ghd7 ‐ or DTH8 ‐deficient backgrounds (Nemoto et al ., 2016; Du et al ., 2017; Zhang et al ., 2017; Zong et al ., 2021). Transcriptional analyses revealed that Ghd7 and Hd1 do not regulate each other’s transcription levels, suggesting that the observed genetic interaction might occur post‐transcriptionally (Nemoto et al ., 2016).…”
Section: Transcriptional and Post‐transcriptional Regulation Of Key Hmentioning
confidence: 99%
See 2 more Smart Citations